If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9t + (3f) * t + 13 = 0 Remove parenthesis around (3f) 9t + 3f * t + 13 = 0 Multiply f * t 9t + 3ft + 13 = 0 Reorder the terms: 13 + 3ft + 9t = 0 Solving 13 + 3ft + 9t = 0 Solving for variable 'f'. Move all terms containing f to the left, all other terms to the right. Add '-13' to each side of the equation. 13 + 3ft + -13 + 9t = 0 + -13 Reorder the terms: 13 + -13 + 3ft + 9t = 0 + -13 Combine like terms: 13 + -13 = 0 0 + 3ft + 9t = 0 + -13 3ft + 9t = 0 + -13 Combine like terms: 0 + -13 = -13 3ft + 9t = -13 Add '-9t' to each side of the equation. 3ft + 9t + -9t = -13 + -9t Combine like terms: 9t + -9t = 0 3ft + 0 = -13 + -9t 3ft = -13 + -9t Divide each side by '3t'. f = -4.333333333t-1 + -3 Simplifying f = -4.333333333t-1 + -3 Reorder the terms: f = -3 + -4.333333333t-1
| 27-×/4=x/5 | | 4+7x-3=9x+13-6x | | 6j+-2j+14j-7j+-9n-(-19)=-15 | | m(a+5)=Kfora | | -0.1x^2-x+31=0.1x^2+2x+11 | | 6j+-2j+14j-7j+-9-(-19)=-15 | | 0.2x^2+x-20=0 | | 6j+-2j+14j-7j+(-19)=-15 | | 6j+2j+14j-7j+(-19)=-15 | | r-r+5r-2r=9 | | -5c+14c+-7=11 | | 5b-19b-(-20b)-(-14)=-10 | | 32+0.90m=2(31+0.30m) | | 20m-10m+2m-8m+2m=6 | | 5u+4u-6u-u=12 | | n^2-n-480=0 | | log(base)2(x^2-3x-66)=2 | | 20n-12n+-9n=8 | | 2x=17+2 | | -3h+-h+6h+-7h=15 | | 5x+26=10x-10 | | -3h+-h+6h+7h=15 | | 8x-4+4x+28=5x+10 | | 2y=3+6y | | 14p+3p-17p+p+p=20 | | 900n-360=0 | | 8x-4=5x+10 | | 8x-4+5x+10=4x+28 | | 5(x+3)+8=-2(x-8) | | 3r+-16r+9r=4 | | 8x-4=5x+10+4x+28 | | 3r+16r+9r=4 |